Reproductive effects of chronic oral exposure to glyphosate under environmentally relevant conditions: an experimental study - Simões, Jamile Silveira Tomiazzi; Bastianini, Mariana Esperendi; Silva, Jaqueline Nascimento; Rossi, Renata Calciolari; Favareto, Ana Paula Alves (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Glyphosate is among the most widely used herbicides globally, raising concerns about its potential adverse health effects. This study aimed to evaluate the reproductive effects of chronic consumption of feed contaminated with glyphosate herbicide in rats. Rats received feed sprayed with glyphosate solution at different concentrations: 0 (control group - CG), 2069 (low concentration group - LCG), 3463 (medium concentration group - MCG), or 5166 ppm per day (high concentration group - HCG) for 180 days. Glyphosate impaired sperm quality. The percentage of sperm with progressive and non-progressive motility and sperm count in the testis was reduced in the two highest exposure groups (MCG and HCG). There was an increase in pinhead and abnormal head and isolated and coiled tail abnormalities in all three exposed groups, with a significant reduction in the number of normal sperm. The integrity of the sperm plasma membrane was not affected by the herbicide. Chronic oral exposure to glyphosate at different concentrations caused alterations in the morphology of adult rat sperm. These findings are crucial as they suggest that prolonged exposure to glyphosate may have detrimental implications on male fertility, highlighting the need for continuous reviews of herbicide use practices and health risk assessments.